2003
DOI: 10.1002/jcp.10462
|View full text |Cite
|
Sign up to set email alerts
|

S100B causes apoptosis in a myoblast cell line in a RAGE‐independent manner

Abstract: S100B, a Ca(2+)-modulated protein with both intracellular and extracellular regulatory roles, is most abundant in astrocytes, is expressed in various amounts in several non-nervous cells and is also found in normal serum. Astrocytes secrete S100B, and extracellular S100B exerts trophic and toxic effects on neurons depending on its concentration, in part by interacting with the receptor for advanced glycation end products (RAGE). The presence of S100B in normal serum and elevation of its serum concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 75 publications
(126 reference statements)
3
49
0
Order By: Relevance
“…30 Alternatively, S100B may induce apoptosis in a RAGEindependent manner by interacting with an unidentified receptor, as has been reported in myoblast cell lines via stimulation of reactive oxygen species production and inhibition of the prosurvival kinase ERK1/2. 32 Finally, the present studies do not exclude that the intracellular effects of S100B may themselves modulate the apoptotic response of postinfarct myocytes. In total, S100B expression after infarction may modulate global remodeling by distinct intracellular and extracellular mechanisms that regulate both myocyte growth and apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…30 Alternatively, S100B may induce apoptosis in a RAGEindependent manner by interacting with an unidentified receptor, as has been reported in myoblast cell lines via stimulation of reactive oxygen species production and inhibition of the prosurvival kinase ERK1/2. 32 Finally, the present studies do not exclude that the intracellular effects of S100B may themselves modulate the apoptotic response of postinfarct myocytes. In total, S100B expression after infarction may modulate global remodeling by distinct intracellular and extracellular mechanisms that regulate both myocyte growth and apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…However, the involved signaling molecules and their mediated signaling pathways are not clear. In endothelial cells, studies found that ligation of RAGE results in a disruption of the monolayer barrier function (26), leading to increasing endothelial permeability through activation of p38 MAPK (64) and protein kinase C (65). Because in epithelium, RAGE is localized juxtapose to the apical cell junctions, it would be interesting to know whether interactions of RAGE with CD11b/CD18 during PMN transmigration would initiate similar downstream signals that interfere the epithelial junction/barrier functions and thereby open the way for PMN to migrate across.…”
Section: Figurementioning
confidence: 99%
“…Several studies support the notion that extracellular S100 proteins may have distinct functions in cellular physiology and pathology. For example, S100A4 was reported to stimulate the outgrowth of neurite cells (Novitskaya et al, 2000), whereas S100B has been shown to be involved in the regulation of cell differentiation and survival (Huttunen et al, 2000;Sorci et al, 2003;Sorci et al, 2004a;Sorci et al, 2004b). Another example is S100A12, which has been implicated as an important pro-inflammatory regulator in numerous chronic inflammatory diseases (Foell et al, 2003a;Foell et al, 2003b;Foell et al, 2003c;Foell et al, 2003d).…”
Section: S100 Camentioning
confidence: 99%
“…Indeed, Roth and co-workers have shown that the S100A12/RAGE interaction plays an important role in the pathology of chronic inflammatory diseases such as bowel disease (Foell et al, 2003c), cystic fibrosis (Foell et al, 2003d), rheumatoid arthritis (Foell et al, 2003b) and vascular disorders (Foell et al, 2003a). Importantly, Donato and colleagues have shown that both RAGE-dependent and -independent extracellular effects of S100B are involved in the regulation of cell survival (Huttunen et al, 2000) and muscle development (Sorci et al, 2003;Sorci et al, 2004a;Sorci et al, 2004b). Although there is no evidence for S100A1 secretion from cardiac cells so far, a release into the extracellular space during myocardial damage has been reported (Kiewitz et al, 2000).…”
mentioning
confidence: 99%